Subcellular localization and visualization of RecA and ImuAʹ in mycobacteria - Ramudzuli, Atondaho Angelah (Division of Medical Microbiology, 2022)
Antibiotic-resistant strains of Mycobacterium tuberculosis (Mtb) are threatening global efforts to eradicate tuberculosis (TB). One attractive approach for target-based drug design proposes to curb the evolution of Mtb during both immune and drug assault. The potential target: mycobacterial DNA metabolism. For this, an in-depth understanding of the mechanisms of DNA repair and mutagenesis in mycobacteria is required. RecA and ImuAʹ are DNA damageinducible proteins implicated in DNA damage repair and tolerance in Mtb. RecA is a key regulatory protein of the SOS response and ImuAʹ is a component of the mycobacterial mutasome, effecting DNA damage tolerance and mutagenesis. In this study, a comprehensive panel of M. smegmatis (Msm) RecA and ImuAʹ reporter strains was generated to explore the dynamics of their expression and subcellular localization within live Msm cells. To this end, fluorescently tagged versions of ImuAʹ and RecA were constructed and shown to retain functional activity in UV-induced mutagenesis but not survival of mitomycin C (MMC) treatment. The discrepant complementation phenotypes observed in UV and MMC assays was unexpected and suggested disruption of a critical protein-protein interaction(s) owing to the presence of the fluorophore. Using fluorescence microscopy, RecA and ImuAʹ expression were monitored in Msm exposed to different types of genotoxic stresses conditions. When mScarletImuAʹ was introduced into wild-type (WT) and ∆imuAʹ backgrounds, diffuse bright red fluorescence was observed in cells treated with MMC and UV; in contrast, no fluorescence expression was observed in untreated cells, confirming the DNA damage-dependent induction of imuAʹ. Following the introduction of RecA-msfGFP into WT and ∆recA backgrounds, discrete green, fluorescent foci were observed in treated and untreated cells in both backgrounds, consistent with the role of RecA in DNA replication in the absence of external DNA damage, and elevated expression under genotoxic conditions. Taken together, these observations support the utility of the fluorescently tagged translational fusions as bioreporters to elucidate the function and regulation of ImuA' and RecA in mycobacteria.